2020
DOI: 10.1111/epi.16714
|View full text |Cite
|
Sign up to set email alerts
|

High concordance between hippocampal transcriptome of the mouse intra‐amygdala kainic acid model and human temporal lobe epilepsy

Abstract: Pharmacoresistance and the lack of disease-modifying actions of current antiseizure drugs persist as major challenges in the treatment of epilepsy. Experimental models of chemoconvulsant-induced status epilepticus remain the models of choice to discover potential antiepileptogenic drugs, but doubts remain as to the extent to which they model human pathophysiology. The aim of the present study was to compare the molecular landscape of the intra-amygdala kainic acid model of status epilepticus in mice with findi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
(136 reference statements)
1
23
0
Order By: Relevance
“…Through these pathways, cAMP regulates fundamental physiological processes such as growth, metabolism, migration, apoptosis, gene transcription, neurotransmission, and plasticity (for review, see [ 44 – 46 ]). Activation of cAMP-responsive element binding protein (CREB)-mediated gene expression could explain histological changes and seizure activity in bPAC mice as the CREB-transcriptional pathway is involved in acute and chronic phases of epilepsy [ 29 , 47 49 ]. A study utilizing transgenic mice with constitutively active CREB showed that chronic elevation of CREB activity in hippocampal principal neurons led to increased excitability of CA1 pyramidal neurons, significant loss of hippocampal neurons, and sporadic epileptic seizures [ 50 ], resembling what we observed in our bPAC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Through these pathways, cAMP regulates fundamental physiological processes such as growth, metabolism, migration, apoptosis, gene transcription, neurotransmission, and plasticity (for review, see [ 44 – 46 ]). Activation of cAMP-responsive element binding protein (CREB)-mediated gene expression could explain histological changes and seizure activity in bPAC mice as the CREB-transcriptional pathway is involved in acute and chronic phases of epilepsy [ 29 , 47 49 ]. A study utilizing transgenic mice with constitutively active CREB showed that chronic elevation of CREB activity in hippocampal principal neurons led to increased excitability of CA1 pyramidal neurons, significant loss of hippocampal neurons, and sporadic epileptic seizures [ 50 ], resembling what we observed in our bPAC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Through these pathways, cAMP regulates fundamental physiological processes such as growth, metabolism, migration, apoptosis, gene transcription, neurotransmission, and plasticity (for review, see Nguyen & Woo, 2003; Cheng et al, 2008; Antoni, 2012). Altered gene expression by activation of cAMP-responsive element (CRE) could explain histological changes and seizure activity in bPAC mice as the CRE-transcriptional pathway is involved in acute and chronic phases of epilepsy (Huang et al, 1994; Hansen et al, 2014; Choi et al, 2016; Conte et al, 2020). The nuclear distribution element-like 1 (NDEL1) protein, transcribed in an activity-dependent manner by the cAMP response element-binding (CREB) protein, has been hypothesized to contribute to pathophysiological alterations of MTLE.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that a total dose of diazepam monotherapy terminated early SE successfully when administered less than 10 min from the beginning of SE. As time went on, gene expression of hippocampal tissue in SE model rats changed [ 20 ]. Thus, SE becomes progressively resistant to benzodiazepine anti-seizure drugs.…”
Section: Discussionmentioning
confidence: 99%